DOI: 10.15368/theses.2013.22
|View full text |Cite
|
Sign up to set email alerts
|

DC, RF, and Thermal Characterization of High Electric Field Induced Degradation Mechanisms in GaN-on-Si High Electron Mobility Transistors

Abstract: Gallium Nitride (GaN) high electron mobility transistors (HEMTs) are becoming increasingly popular in power amplifier systems as an alternative to bulkier vacuum tube technologies. GaN offers advantages over other III-V semiconductor heterostructures such as a large bandgap energy, a low dielectric constant, and a high critical breakdown field. The aforementioned qualities make GaN a prime candidate for high-power and radiation-hardened applications using a smaller form-factor. Several different types of semic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Some examples of these images are shown in Degradation also manifests in a change in the I ds vs. V ds family of curves, discussed more in §5.2, that shows an increase in I ds due to a negative shift in the threshold voltage, V th (this trend is also observed in data presented in §6.1) [18]. …”
Section: Hemt Reliability and Degradation Terminal Characteristicsmentioning
confidence: 58%
See 4 more Smart Citations
“…Some examples of these images are shown in Degradation also manifests in a change in the I ds vs. V ds family of curves, discussed more in §5.2, that shows an increase in I ds due to a negative shift in the threshold voltage, V th (this trend is also observed in data presented in §6.1) [18]. …”
Section: Hemt Reliability and Degradation Terminal Characteristicsmentioning
confidence: 58%
“…One of the most easily observable signs of degradation is increased gate leakage current. Previous research has shown that gate leakage current, I g , increases when exposed to a high electric field (for reasons that will be discussed in subsequent sections) [18], [23]. The change in gate leakage current was found to be dependent on both the gate stress voltage and the amount of time the gate was exposed to the stress [23].…”
Section: Hemt Reliability and Degradation Terminal Characteristicsmentioning
confidence: 81%
See 3 more Smart Citations